ANALISIS STRUKTUR ORGANISASI, SISTEM WEWENANG, PRAKTEK YANG SEHAT, DAN KARYAWAN YANG BERMUTU TERHADAP SISTEM PENGENDALIAN INTERN KAS (Studi PT. Citra Van Tiki Cabang Solo) - Pardi Pardi; Alisa Rusdiana (JURNAL ILMIAH EDUNOMIKA, 2021)
This research was conducted with the aim to knowing the effect of organization structure, system of authority / authorization, healthy practice, and quality employees on the internal cash control system. The approach used in this study is quantitative, using 566 employee population who actively attend monthly meetings at PT. Citra Van Tiki Solo Branch. Samples using the Slovin formula, obtained amounted to 85 people. The data analysis technique used test instruments, namely; validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, Autocoleration test, multiple linear regression, F test, t test, and determination test (R2) which were processed using SPSS 21.0 program. The results showed that the organization structure, system of authority, healthy practice, and quality employees partially affected the internal cash control system. Keywords : Organization Structure, System of Authority, Healthy Practice, Quality Employees.